Method of Nickel Extraction from Industrial Waste and its Application in Production: Metode Ekstraksi Nikel dari Limbah Industri dan Penerapannya dalam Produksi - Bekhzod Farmanov Ilkhomovich; Tavashov Shakhzod Khujaxmatovich (Universitas Muhammadiyah Sidoarjo, 2022)
The article describes the process of extracting nickel from the composition of the used waste of the GIAP-8 catalyst in the form of nickel nitrate, in which it not only does not affect the environmental environment, but is also a cost-effective solution for the production of nickel catalysts. The obtained catalysts were tested in laboratory conditions, the activity of the catalyst in this converted residual methane was 35,7% at T =500 °C and 6,5% at T= 700 °C.